KEBIJAKAN PENDIDIKAN ISLAM DI MASA ORDE BARU DALAM MENGATASI KRISIS ULAMA: KAJIAN HISTORIS LAHIRNYA MAPK - Miftahul Huda (Universitas Islam Lamongan, 2022)
The New Order gave a new style to the policy of Islamic religious education due to the shift in the influence of communism towards strengthening Pancasila through a sustainable national development plan. This article aims to examine the influence of Islamic education policies during the New Order era on the existence of madrasas. The method used in this study is qualitative with historical and policy analytical methods. This study found that the policy of Islamic education during the New Order era was religious education, and religious education institutions were encouraged to participate in national development. Meanwhile, the influence of Islamic education policies during the New Order era on the existence of madrasas was an innovation to restore the function of madrasas as places to print religious leaders, namely by opening an alternative Madrasah Aliyah named Madrasah Aliyah Special Program (MAPK). The presence of MAPK is essentially a form of progressive, positive response of madrasas to the challenges they face, namely in overcoming the crisis of ulama.The New Order gave a new style to the policy of Islamic religious education due to the shift in the influence of communism towards strengthening Pancasila through a sustainable national development plan. This article aims to examine the influence of Islamic education policies during the New Order era on the existence of madrasas. The method used in this study is qualitative with historical and policy analytical methods. This study found that the policy of Islamic education during the New Order era was religious education, and religious education institutions were encouraged to participate in national development. Meanwhile, the influence of Islamic education policies during the New Order era on the existence of madrasas was an innovation to restore the function of madrasas as places to print religious leaders, namely by opening an alternative Madrasah Aliyah named Madrasah Aliyah Special Program (MAPK). The presence of MAPK is essentially a form of progressive, positive response of madrasas to the challenges they face, namely in overcoming the crisis of ulama.